Net Neutrality in the Context of Provision of Fair and Equitable Access to Information Sources and Services. Issue 1 (2nd January 2019) - Novak, Amanda; Hajibayova, Lala
ABSTRACT: The purpose of this literature review is to examine the impact of changes in net neutrality policies on public library services. Specifically, this review aims to find what questions have been investigated in relation to public library institutions and their users. Reviewed literature seems to be in favor of a neutral Internet and argues about the negative effects of its loss. Librarians whose mission is to protect disenfranchised members of society seemed to be motivated to fight for a neutral Internet and favor of keeping net neutrality policies in place.